Functional Evaluation of High Volume Pavements using Network Survey Vehicle - Verma, Anand (My University, 2022)
This study attempts to study the functional parameters of pavements like roughness, rutting and texture which also includes various pavement distress like Cracking, ravelling etc. In addition, the study also focus on the importance of the Network survey vehicle and the how the NSV operates on the road at a high speed while analyzing the various parameters (mentioned above), saving the time and improving the accuracy of the data captured. For this study, few National Highways were selected while undergoing internship at G-Eng Advisory Services Private Ltd. Different type of national highways like flexible pavement, mix roads(flexible and rigid pavements), Expressways, mountainous roads to analyze the working of NSV at different site conditions. The data is presented in accordance of National Highway Authority of India (NHAI) i.e RIS templates which is uploaded on the RAMS site of NHAI which helps the authority to make a maintenance plan for the pavement using HDM-4. In addition, conclusion is also added in the form of summary length for roughness and rutting for better assessment of the present condition of the pavement.
Keywords: Network Survey Vehicle; ROMDAS; HDM-4; Roughness; Rutting